The metaphysics of hyperspace - Hudson, Hud. (Oxford : Clarendon, 2005)
Hud Hudson offers an examination of philosophical reasons to believe in hyperspace. He explores non-theistic reasons, then inquires into a variety of puzzles in the metaphysics of material objects that are generated by the hypothesis of hyperspace or informed by it. Finally, he explores theistic reasons.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics; Fourth dimension